PANCASILA DALAM PERSPEKTIF HUKUM KONSTITUSI INDONESIA - Fadli Andi Natsif (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2017)
In the perspective of constitutional law, the affirmation of Pancasila as the basis and ideology of the nation and state of Indonesia is very clearly embodied in the Preamble of the 1945 Constitution. It is not necessary to be poured through the Act or MPR Tap, whose position can be changed someday and even abolished. Thus, the recognition of Pancasila's very firm and clear position brings the consequence that Pancasila must also function as a guideline (base and direction) in preparing all policies to be taken by the Indonesian government.Keywords: Pancasila, Indonesian Constitutional Law Dalam perspektif hukum konstitusi, penegasan Pancasila sebagai dasar serta ideologi bangsa dan negara Indonesia sudah sangat jelas termaktub dalam Pembukaan UUD 1945. Tidak perlu lagi dituangkan melalui UU atau Tap MPR, yang kedudukannya suatu saat bisa diubah bahkan dihapuskan. Dengan demikian, pengakuan kedudukan Pancasila yang sudah sangat tegas dan jelas ini membawa konsekuensi bahwa Pancasila harus pula difungsikan sebagai pedoman (dasar dan haluan) dalam menyusun segala kebijkan yang akan diambil oleh pemerintah Indonesia.Kata kunci : Pancasila, Hukum Konstitusi Indonesia